The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus - França, Diogo; Paprocki, Henrique (Zootaxa, 2019)
The Macrostemum Kolenati is a conspicuous genus of Trichoptera containing 18 species in the Neotropical region. This study designates a neotype of Macrostemum hyalinum, the type species of the genus, establishes the Atlantic Forest of Espirito Santo, Brazil, as the species type locality, and proposes a key to males of Neotropical species in this genus.